An Analysis of Referential Cohesive Devices Used in Songs Written by "Maher Zain" - Khairun Nasir; Sarah Nadia; Ayu Nindia (Modality Journal: International Journal of Linguistics and Literature, 2022)
The study entitled“An Analysis of Referential Cohesive Devices used in Songs Written by "Maher Zain". This study aimed to find out and describe the types of referential cohesive devices used in the songs, and to explain the pattern of referential cohesive devices that were delivered in Maher Zain’s songs lyric. This study used qualitative approach with library research where Halliday and Hasan’s theory was used to answer the problem of the research. The data was analyzed by using Miles, Huberman, and Saldana’s data analysis technique: data condensation, data display, and conclusion drawing or verification. The researcher generated results from tables that accompanied by various type of referential cohesive devices used in the songs. The researcher chose seven songs from Salam album that were written by Maher Zain. The findings were shown that there were 62 words based on personal reference which including 46 words for existential cohesive devices, 16 words for possessive determiners and there was no for the type of possessive pronoun. There were 11 words for demonstrative reference including 1 word for adverbial demonstrative reference and 10 words for selective nominal demonstrative reference.Penelitian yang berjudul “Analisis Perangkat Kohesif Referensial yang Digunakan Dalam Lagu Karya “Maher Zain”. Penelitian ini bertujuan untuk mengetahui dan mendeskripsikan jenis-jenis perangkat kohesif referensial yang digunakan dalam lagu, serta menjelaskan pola perangkat kohesif referensial yang dibawakan dalam lirik lagu Maher Zain. Penelitian ini menggunakan pendekatan kualitatif dengan studi pustaka dimana teori Halliday dan Hasan digunakan untuk menjawab permasalahan penelitian. Teknik analisis data menggunakan teknik analisis data Miles, Huberman, dan Saldana: kondensasi data, penyajian data, dan penarikan kesimpulan atau verifikasi. Peneliti menghasilkan hasil dari tabel yang disertai dengan berbagai jenis perangkat kohesif referensial yang digunakan dalam lagu. Peneliti memilih tujuh lagu dari album Salam yang ditulis oleh Maher Zain. Hasil penelitian menunjukkan bahwa berdasarkan referensi pribadi terdapat 62 kata yang meliputi 46 kata untuk perangkat kohesif eksistensial, 16 kata untuk penentu posesif dan tidak ada untuk jenis kata ganti posesif. Ada 11 kata untuk referensi demonstratif termasuk 1 kata untuk referensi demonstratif adverbial dan 10 kata untuk referensi demonstratif nominal selektif.